Perbandingan Penerapan Pembelajaran Kooperatif Tipe Jigsaw Dengan TAI Terhadap Hasil Belajar Ranah Kognitif Kelas Viii [A Comparison of the Implementation of Cooperative Learning Methods Jigsaw and TAI on Cognitive Learning Outcomes of Grade 8 Students] - Susilawati, Yuni Eka; Silalahi, Desri Kristina; Saragih, Melda Jaya (JOHME: Journal of Holistic Mathematics Education, 2017)
One of the factors affecting student learning outcomes is the learning process in the classroom. A teacher-centered learning process provides little learning experience for students. Student-centered learning needs to be developed so that students may experience meaningful learning and achieve good outcomes. The purpose of this study was to see the different cognitive learning outcomes caused by the implementation of two cooperative learning methods: jigsaw and TAI. The research method used is a quantitative quasi experiment with Nonequivalent Control Group Design. Student learning outcomes were measured by a post test. The difference in the learning outcomes were tested using a t-test. The research concludes that there is a significant difference of cognitive learning outcomes between students who are given cooperative learning jigsaw type (mean 43.14) and TAI (mean 47.85).ABSTRAK BAHASA INDONESIA: Salah satu faktor yang memengaruhi hasil belajar siswa adalah proses pembelajaran di kelas. Pembelajaran yang berpusat kepada guru cenderung memberikan sedikit pengalaman belajar kepada siswa. Pembelajaran yang berpusat kepada siswa perlu dikembangkan agar siswa dapat mengalami pembelajaran yang bermakna dan mendapatkan hasil belajar yang baik. Tujuan penelitian ini untuk melihat perbedaan hasil belajar kognitif karena penerapan dua jenis pembelajaran kooperatif yaitu jigsaw dan TAI pada dua kelas yang berbeda. Metode penelitian yang digunakan adalah kuantitatif quasi eksperimen dengan desain penelitian Nonequivalent Control Group Design. Hasil belajar siswa diukur menggunakan nilai post-test. Perbedaan hasil belajar  dianalisis menggunakan uji t.  Hasil penelitian menunjukkan bahwa terdapat perbedaan signifikan (hasil belajar ranah kognitif antara siswa yang diberikan pembelajaran kooperatif tipe jigsaw (mean 43.14) dengan tipe TAI (mean 47.85).